2017
DOI: 10.1182/blood-2016-11-751065
|View full text |Cite
|
Sign up to set email alerts
|

Invariant NKT cells contribute to chronic lymphocytic leukemia surveillance and prognosis

Abstract: Chronic lymphocytic leukemia (CLL) is characterized by the expansion of malignant CD5 B lymphocytes in blood, bone marrow, and lymphoid organs. CD1d-restricted invariant natural killer T (iNKT) cells are innate-like T lymphocytes strongly implicated in tumor surveillance. We investigated the impact of iNKT cells in the natural history of the disease in the Eμ-Tcl1 (Tcl1) CLL mouse model and 68 CLL patients. We found that Tcl1-CLL cells express CD1d and that iNKT cells critically delay disease onset but become … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
63
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 59 publications
(66 citation statements)
references
References 56 publications
2
63
1
Order By: Relevance
“…In addition, iNKT-cell activation also inhibits tumor-induced myeloid derived suppressor cells (MDSCs) 8 and tumor angiogenesis 12 . Increased numbers of circulating and intra-tumor iNKT cells have been associated with an improved prognosis in different cancers and hematological malignancies, 13,14 supporting the important role of iNKT cells in cancer immunosurveillance and its potential as a promising immunotherapeutic target.…”
Section: Introductionmentioning
confidence: 95%
“…In addition, iNKT-cell activation also inhibits tumor-induced myeloid derived suppressor cells (MDSCs) 8 and tumor angiogenesis 12 . Increased numbers of circulating and intra-tumor iNKT cells have been associated with an improved prognosis in different cancers and hematological malignancies, 13,14 supporting the important role of iNKT cells in cancer immunosurveillance and its potential as a promising immunotherapeutic target.…”
Section: Introductionmentioning
confidence: 95%
“…Interestingly, in chronic lymphocytic leukemia (CLL), CD1d expression was found to increase during disease progression, counteracting the suggested role of CD1d as an anti-survival factor in cancer ( 102 , 103 ). However, a recent study has shown that higher CD1d expression on CLL cells associated with disease progression actually led to impairment in both function and numbers of type I NKT cells ( 104 ). CD1d independent cytotoxic effect of NKT cells on various hematopoietic tumor cell lines have also been reported ( 98 , 105 , 106 ).…”
Section: Direct Cytotoxicity Against Tumor Cellsmentioning
confidence: 99%
“…Unfortunately, no or low clinical benefits were reported among patients (2224). These disappointing results might be due to the lower number of NKT cells in patients relative to healthy individuals and/or to their diminished (but reversible) activation threshold capacity (2232). Hence, one concern in NKT cell-based therapy is the diminished NKT cell count and/or function, although this cannot be generalized to all advanced cancer patients.…”
Section: Free α-Galcer In Antitumor Therapy: From Preclinical Studiesmentioning
confidence: 99%